ELIMINIT: Combating Nitrite in Edible Bird Nest - Saiful Nizam, Tajuddin; Nurul ‘Azyyati, Sabri; Nazira, Mahmud; M. M., Yusoff; Lee, Chin Mei; Maizatul Farhain, Ismail (2015)
Swiftlet farming industry is a very profitable investment for those that are successful. The demand for edible bird’s nest from China, Hong Kong, Taiwan, Japan, South Korea, India and the Middle Eastern countries is increasing. Swiftlet industry in Malaysia is facing difficult time since August 2011 because Chinese government has banned on edible bird’s nest and its products from Malaysia. This is due to high level of nitrite (NO2) spotted in edible bird’s nest (AQSIQ, 2011). As the consequences, the edible bird’s nest and swiftlet ranching industry in Malaysia has been hit hard. So, to meet the standard of Chinese government, an investigation is proposed by using indigenous microorganisms (IMO) technology for nitrite elimination in edible bird’s nest of swiftlet.